2010
DOI: 10.1016/j.ejpain.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Central pain in multiple sclerosis – Sensory abnormalities

Abstract: Many patients with multiple sclerosis (MS) develop central neuropathic pain (CP). In the present study somatosensory abnormalities have been analysed in detail in 62 patients with MS and CP (42 women, 20 men; mean age 52 years) and in a control group of 10 women and 6 men (mean age 47 years) with MS and sensory symptoms, but without pain. Assessment included clinical testing and quantitative methods (QST) for the measurement of perception thresholds for touch, vibration, and temperatures. All CP patients excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 37 publications
(73 reference statements)
4
55
0
1
Order By: Relevance
“…From a fundamental point of view, determining the exact sensory mechanisms involved in skin wetness perception represents a way to gain conceptual and functional understanding of somatosensory integration under normal brain function. Clinically, as numerous neurological disorders, amongst which multiple sclerosis, are characterized by the development of sensory abnormalities in the form of burning sensations across the body, paradoxical wetness sensations, and decreased detection thresholds for cold and warm temperatures (132,136,236,283), it is clear how increasing the fundamental knowledge on human somatosensory integration could improve our understanding of the link between neurological disease and altered somatosensory function.…”
Section: Neurophysiology Of Skin Wetness Perceptionmentioning
confidence: 99%
“…From a fundamental point of view, determining the exact sensory mechanisms involved in skin wetness perception represents a way to gain conceptual and functional understanding of somatosensory integration under normal brain function. Clinically, as numerous neurological disorders, amongst which multiple sclerosis, are characterized by the development of sensory abnormalities in the form of burning sensations across the body, paradoxical wetness sensations, and decreased detection thresholds for cold and warm temperatures (132,136,236,283), it is clear how increasing the fundamental knowledge on human somatosensory integration could improve our understanding of the link between neurological disease and altered somatosensory function.…”
Section: Neurophysiology Of Skin Wetness Perceptionmentioning
confidence: 99%
“…Although other factors need to be considered, such as omega 3 and vitamin D deficiency (refer to paper by Simpson et al in this issue), environmental and genetic factors [75][76][77][78]. Nevertheless, further research is required to determine if there is a link between vitamin B12 and MS. [83,87,88] Visual impairment that causing double vision, inability to focus on the object, optical motor function dysregulation [89] Visual impairment that causing double vision, inability to focus on the object, optical motor function dysregulation [90][91][92] Cranial nerve damage, including thermoregulation, sensory, audiooptical-gustatory impairments, dysarthria [89] Cranial nerve damage, including thermoregulation, sensory, audiooptical-gustatory impairments, dysarthria [93][94][95][96] Tingling sensations, tremor, numbness of the limbs, involuntary movements [97] Tingling sensations, tremor, numbness of the limbs [98][99][100][101] Muscular pain and spasm [97,102] Muscular pain and spasm [3,84] Smooth muscles malfunction, including swallowing difficulty [103] Smooth muscles malfunction, including swallowing difficulty [104,105] Fatigue, lack of energy and weakness [106] Fatigue, lack of energy and general weakness [107][108][109][110][111] Bladder and sexual incontinence [112,113] Bladder and sexual dysfunctions [114]…”
Section: Vitamin B12 Deficiency and Ms Symptoms: Similarities And Difmentioning
confidence: 99%
“…Pain prevalence in MS ranges from 25-90% (8,36,37), depending upon the assessment protocols used and the definition of pain being applied (34). MS-induced chronic neuropathic pain is typically associated with significant MS-related disability and depression (38) and pain syndromes can be divided into primary pain caused directly by demyelination, neuroinflammation, and/or axonal damage in the CNS from disease, or into secondary pain due to an indirect consequence of the CNS lesion (8,39). Interestingly, recent imaging studies showed that demyelinating lesions are most commonly reported in the brainstem and less commonly in the spinal cord.…”
Section: Multiple Sclerosis-induced Neuropathic Pain Pathophysiology mentioning
confidence: 99%
“…Other forms of neurogenic pain, including migraine with or without aura and tension-type headache, seem to be more prevalent in MS patients than in the general population (44). Dysaesthetic extremity pain is often characterized as a continuous burning, tingling, or aching dysaesthesia, predominantly in the legs and feet that is often worse at night and can be exacerbated by physical activity (8,34,39). In patients with MS, dysaesthetic extremity pain is the most commonly reported type of neuropathic pain, having a prevalence of 12-28% (45,46).…”
Section: Multiple Sclerosis-induced Neuropathic Pain Pathophysiology mentioning
confidence: 99%